A study of marine environmental protection and biodiversity observation and monitoring mechanisms in Taiwan - Shih, Yi-Che (Frontiers in Marine Science, 2025)
Taiwan’s marine ecosystems are increasingly vulnerable to anthropogenic and environmental pressures, highlighting the urgent need for effective biodiversity monitoring. This study investigates existing marine biodiversity observation and monitoring mechanisms in Taiwan to inform future conservation and policy development. The study analyzes three long-term ecological datasets: (1) plankton assemblages in western coastal waters (1993–2021), (2) fish assemblages in northern rocky tide pools, and (3) fish assemblages in southern tide pools. Additionally, it evaluates the Taiwan Marine Environment Monitoring Service (TwMEMS), which integrates real-time and historical oceanographic data for ecological assessment and disaster preparedness. The findings reveal distinct seasonal and regional biodiversity patterns. Plankton communities exhibited peak chlorophyll-a concentrations in the third quarter, indicating nutrient enrichment likely from upwelling or runoff. Fish assemblages showed site-specific species richness, with notable dominance of Bathygobius fuscus and Istiblennius species. TwMEMS data demonstrated improved tsunami detection through advanced filtering techniques, supporting ecosystem risk monitoring. Taiwan’s monitoring systems provide valuable baseline data for assessing long-term ecological change but face challenges in data integration and indicator standardization. Strengthening these frameworks through regional monitoring hubs, standardized biodiversity indicators, and alignment with international platforms such as GBIF and BONs will enhance marine conservation effectiveness. This study emphasizes the role of integrated observation mechanisms in supporting ecosystem-based management and Taiwan’s contribution to global biodiversity goals.